Elucidation of sterol biosynthesis pathway and its co-regulation with fatty acid biosynthesis in the oleaginous marine protist Schizochytrium sp. - Bi, Yali; Guo, Pengfei; Liu, Liangsen; Chen, Lei; Zhang, Weiwen (Frontiers in Bioengineering and Biotechnology, 2023)
Sterols constitute vital structural and regulatory components of eukaryotic cells. In the oleaginous microorganism Schizochytrium sp. S31, the sterol biosynthetic pathway primarily produces cholesterol, stigmasterol, lanosterol, and cycloartenol. However, the sterol biosynthesis pathway and its functional roles in Schizochytrium remain unidentified. Through Schizochytrium genomic data mining and a chemical biology approach, we first in silico elucidated the mevalonate and sterol biosynthesis pathways of Schizochytrium. The results showed that owing to the lack of plastids in Schizochytrium, it is likely to employ the mevalonate pathway as the terpenoid backbone pathway to supply isopentenyl diphosphate for the synthesis of sterols, similar to that in fungi and animals. In addition, our analysis revealed a chimeric organization of the Schizochytrium sterol biosynthesis pathway, which possesses features of both algae and animal pathways. Temporal tracking of sterol profiles reveals that sterols play important roles in Schizochytrium growth, carotenoid synthesis, and fatty acid synthesis. Furthermore, the dynamics of fatty acid and transcription levels of genes involved in fatty acid upon chemical inhibitor-induced sterol inhibition reveal possible co-regulation of sterol synthesis and fatty acid synthesis, as the inhibition of sterol synthesis could promote the accumulation of fatty acid in Schizochytrium. Sterol and carotenoid metabolisms are also found possibly co-regulated, as the inhibition of sterols led to decreased carotenoid synthesis through down-regulating the gene HMGR and crtIBY in Schizochytrium. Together, elucidation of the Schizochytrium sterol biosynthesis pathway and its co-regulation with fatty acid synthesis lay the essential foundation for engineering Schizochytrium for the sustainable production of lipids and high-value chemicals.